2022
DOI: 10.1002/prep.202100335
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition Performance of CL‐20‐Based Ultraviolet Curing Propellants

Abstract: Photocuring formulas were designed for 3D printing technology used in forming propellants, explosives, and pyrotechnics. Thermal performance is an essential part of the comprehensive performance of this kind of formula. In this paper, a formula consisting of epoxy acrylic resin (EA) as binder and hexanitrohexaazaisowurtzitane (CL‐20) as the energetic additive was developed and printed by material extrusion 3D printing technology. The thermal decomposition behavior was investigated by the differential scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Whereas XPS can only be used to characterize the surface of a sample, the entire sample is characterized by thermal analysis; thus, a significantly smaller mass percentage of cg-N is determined by thermal analysis than by XPS. The original exothermic peaks were divided into two peaks based on a Bigaussian function [ 47 ] to determine the ratios of the quantity of heat released by the various components, where the curves with the fitted peaks are presented in Figure 8 b. Comparing the integration areas of the different curves results in an almost 3:2 ratio for the heat released by cg-N to that of NaN 3 with the CNT substrate in an argon gas atmosphere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas XPS can only be used to characterize the surface of a sample, the entire sample is characterized by thermal analysis; thus, a significantly smaller mass percentage of cg-N is determined by thermal analysis than by XPS. The original exothermic peaks were divided into two peaks based on a Bigaussian function [ 47 ] to determine the ratios of the quantity of heat released by the various components, where the curves with the fitted peaks are presented in Figure 8 b. Comparing the integration areas of the different curves results in an almost 3:2 ratio for the heat released by cg-N to that of NaN 3 with the CNT substrate in an argon gas atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…Molecules 2024, 29, x FOR PEER REVIEW 9 of 13 based on a Bigaussian function [47] to determine the ratios of the quantity of heat released by the various components, where the curves with the fitted peaks are presented in Figure 8b. Comparing the integration areas of the different curves results in an almost 3:2 ratio for the heat released by cg-N to that of NaN3 with the CNT substrate in an argon gas atmosphere.…”
Section: Tg-dsc-ftir-ms Analysismentioning
confidence: 99%
“…LOVA gun propellants were applied in the most mature photocuring 3D printing technology. Studies from foreign institutions have found that low-solid-content propellants and explosives products were prepared with photocuring solidification methods, but as the solid content is improved, the photocuring solidification method is no longer applicable [58] .…”
Section: Figure 15 the Main Component Of The Photocurable Adhesivementioning
confidence: 99%